Analisis Alur Belajar Matematika Siswa Inklusi Jenis Kebutuhan Autisme - Ahmad Lutfi; Alfizah Ayu Indria Sari (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2022)
This study aims to describe the Mathematics Learning Flow of Students' with Inclusion types of Autism Needs in the Material of Addition and Subtraction of Numbers up to Two Numbers. This type of research is qualitative research. The instrument in this study is the researcher himself. Other instruments that support obtaining data are problem-solving tasks and interview guidelines to reveal the flow of students' mathematics learning inclusion types of autism needs. The subjects in this study were two students who included autism needs type, respectively male and female. Based on the results of the analysis that has been carried out by providing problem-solving problems in the form of mathematical problems and being strengthened by conducting interviews, it was found that the type of autism needed with the category of High Functioning Autism followed every step of Polya’s problem solving and in the student's thinking process occurred assimilated. Meanwhile, children with autism needs with the category of Low Functioning Autism do not follow every step of Polya’s problem-solving, and in the process of thinking, this student is likely to accommodate a scheme about simple data that is clearly stated in the problem.(Penelitian ini bertujuan untuk mendeskripsikan Alur Belajar Matematika Siswa Inklusi Jenis Kebutuhan Autisme Pada Materi Penjumlahan dan Pengurangan Bilangan Sampai Dua Angka. Jenis penelitian menggunankan metodologi penelitian kualitatif deskriptif. Instrumen utama pada penelitian ini adalah peneliti sendiri. Instrument lainnya yang mendukung dalam mendapatkan data adalah tugas pemecahan masalah dan pedoman wawancara untuk mengungkapkan alur belajar matematika siswa inklusi jenis kebutuhan autisme. Subjek dalam penelitian ini adalah dua orang siswa inklusi jenis kebutuhan autisme masing-masing laki-laki dan perempuan. Berdasarkan hasil analisa yang telah dilakukan dengan memberikan soal pemecahan masalah berupa soal matematika dan diberi penguatan dengan melakukan wawancara didapatkan bahwa anak dengan kebutuhan autism kategori high functioning autism mengikuti setiap langkah pemecahan masalah menurut Polya dan proses berfikir siswa tersebut terjadi secara asimilasi. Sedangkan anak dengan kebutuhan autism kategori Low Functioning Autism tidak mengikuti setiap langkah pemecahan masalah Polya dan proses berfikir siswa ini cendrung mengakomodasi skema tentang data sederhana yang secara jelas dinyatakan dalam soal).